ORDERING INFORMATION SYSTEMS DESIGN AND DELIVERY OF GOODS IN. MEIJI INDONESIA - Popy Indrasari; Eko Hadiyanto, Drs., MM Eko Hadiyanto, Drs., MM (Jurnal Sistem Informasi, 1998)
Existence of ordering and delivery system plays a very important for the survival ofan enterprise, especially when the system / management control is managed andconducted properly in accordance with the regulations set by the company.for the purpose of writing this paper tries to provide an information system designand ordering a new shipment so that delivery of information to be efficiently andeffectively so that the activities of these companies can continue to run and all theobstacles faced by these companies may soon be overcome and can meet needs.